Effectiveness of the 4-7-8 Breathing Technique in Enhancing Sleep Quality for COPD Patients - Satria, Orita; Nasution, Nurromsyah; Apriani, Fitri; Andriani, Rizki; Damayanti, Siti; Permatasari Tarigan, Amira (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a disease that is a health problem throughout the world. COPD sufferers can experience problems with decreased oxygen levels. This incidence can cause COPD sufferers to experience decreased sleep quality. Poor sleep quality will have an impact on the sufferer's physiology. Therefore, COPD sufferers can do breathing exercises, such as the 4-7-8 breathing exercises, which play a role in maximizing oxygen in the respiratory system. This study was conducted to determine the effect of 4-7-8 breathing exercises on improving sleep quality in patients with COPD Method: This study used a quasi-experimental design with a pretest-posttest without a control. This research was conducted on 45 samples, which were recruited in Cut Nyak Dhien Regional Hospital's pulmonary polyclinic, from February 29 to March 18, 2024. The main interventions carried out are the 4-7-8 breathing technique, and the study tool is the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data analysis method used was the Wilcoxon statistical test. Results: There is a decrease from 13.33 (pre-intervention) to 4.93 (post-intervention) for the mean score of the breathing exercise 4-7-8. There is a significant influence between influence of the 4-7-8 breathing exercise on improving sleep quality in COPD patients (P=0.001). Conclusion: There is a significant effect of breathing exercise 4-7-8 on improving sleep quality in COPD patients.